Multistage ROS-Responsive and Natural Polyphenol-Driven Prodrug Hydrogels for Diabetic Wound Healing - Ni, Zhipeng; Yu, Haojie; Wang, Li; Huang, Yudi; Lu, Hui; Zhou, Haiying; Liu, Qingxian (ACS applied materials & interfaces, 2022)
The high level of reactive oxygen species (ROS) and bacterial infection impede wound healing of the diabetic wound. Here, benefiting from the antioxidation effects of tannic acid (TA) and ROS-responsive phenylborate ester (PBAE), a series of ROS-responsive anti-inflammatory TA-conjugated nanoparticle hydrogels (PPBA-TA-PVA) can be obtained by conveniently mixing TA, phenylboric acid modified polyphosphazene (PPBA), and poly(vinyl alcohol) (PVA). The obtained PPBA-TA-PVA hydrogels could effectively inhibit the growth of Escherichia coli (antibacterial rate = 93.1 ± 1.1%) within 4 h and effectively scavenge both 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and •OH radicals in vitro. Besides, the cell migration rate of HDFa cells treated with PPBA-TA-PVA hydrogels (84.2 ± 4.6%) was twice the rate of normal cells (43.8 ± 8.1%) after 24 h of cocultivation. The clinical relevance was demonstrated further by assessing the PPBA-TA-PVA hydrogels in full-thickness excisional wounds in a streptozotocin (STZ)-induced diabetic rat model. The PPBA-TA-PVA hydrogels could act as effective ROS-scavenging agents to alleviate inflammation and accelerate wound closure by decreasing the proinflammatory cytokines (IL-6, IL-1β) and increasing the gene expression of TGF-β1, COL-1, and COL-3, which resulted in faster re-epithelialization and increased formation of granulation tissue.